Reframing purpose and conceptions of success for a post-Covid-19 South African higher education - Laura Dison; Kershree Padayachee; Danie de Klerk; Willem Conradie; Fiona MacAlister; Shirra Moch; Greig Krull (University of Johannesburg, 2022)
The Covid-19 pandemic raised immense challenges for universities. Staff and students had to quickly transition to an unfamiliar mode of emergency remote teaching and learning (ERTL) with its associated affordances and losses. The experiences of students and staff and the lessons learned during this time will affect the provision of teaching and learning in the future. During ERTL, a group of academics and teaching and learning support staff from different faculties at a large research-intensive public university in South Africa came together to support each other and share experiences of enhancing teaching and learning in higher education. This led to reflection on the impact of Covid-19 on the higher education landscape through community of practice. The aim of this conceptual paper is to discuss alternative notions of institutional purpose and lecturers' conception of success that might influence the emerging post-Covid-19 higher education landscape in the global south. We claim that a more nuanced and critical understanding of these concepts is essential to evaluate the gains and losses experienced during Covid-19. Our argument hinges on our reflections of supporting teaching and learning during 2020 and 2021, and our observations of the challenges experienced by lecturers as they transitioned to ERTL. We suggest that it was in the moments of disruption and disequilibrium that lecturers were required to re-think the purpose of their courses and of higher education more broadly. Furthermore, it challenged us as a collective and individually to reflect critically on the measures of success within courses that changed dramatically in response to the prevailing circumstances, as well as more broadly within the sector.